The cardiac MRI substudy to ongoing telmisartan alone and in combination with ramipril global endpoint trial/telmisartan randomized assessment study in ACE-intolerant subjects with cardiovascular disease: Analysis protocol and baseline characteristics - Cowan, B.; Young, A.; Anderson, C.; Doughty, R.; Krittayaphong, R.; Lonn, E.; Marwick, T.; Reid, Christopher; Sanderson, J.; Schmieder, R.; Teo, K.; Wadham, A.; et al. (2009)
Background: The ONTARGET and TRANSCEND clinical trials were designed to investigate the cardioprotective effects of telmisartan 80 mg and ramipril 10 mg, alone and in combination, in patients at high risk of cardiovascular disease. Cardiac MRI enables investigation of mechanistic effects of these agents on cardiac structural and functional variables. Here, we report the design, analysis protocol, reproducibility and relevant quality control procedures, and baseline patient characteristics of the ONTARGET/TRANSCEND cardiac MRI substudy. MRI was undertaken in 330 subjects enrolled in ONTARGET, and 38 subjects in TRANSCEND, across eight centers in six countries. Analyses were performed by two independent analysts using guide-point modeling. Cases with discrepancies in LV mass (LVM) of >5% were independently reanalyzed. Cases with discrepancies in end-diastolic volume (EDV) of >5%, or end-systolic volume (ESV) of >12%, were then reconciled by consensus. Results: Baseline characteristics were broadly similar to the main ONTARGET/TRANSCEND trials, except for a higher frequency of coronary artery disease and Asian ethnicity in the substudy. Reproducibility of MRI analyses (mean ± SD) were 2.8 ± 3.7 ml in EDV, -0.3 ± 3.6 ml in ESV, 3.1 ± 3.3 ml in SV, 1.1 ± 1.8% in EF, and 0.4 ± 4.5 g in LVM. Subgroup analyses revealed increased ESV and LVM, and reduced EF, in subjects with a history of either coronary artery disease or myocardial infarction. Conclusions: The ONTARGET/TRANSCEND cardiac MRI substudy protocol provides for a reliable assessment of the effects of telmisartan and ramipril, alone and in combination, on cardiac structural and functional parameters over a 2-year follow-up period. © 2009 Springer-Verlag.